Early Childhood Education Teachers Consistency of E-Learning Programs - Yuanita Kristiani Wahyu Widiastuti; Upik Elok Endang Rasmani; Siti Wahyuningsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
The e-learning program is a new program implemented at the early childhood education level. The teacher of the main character in the application of e-learning has a dilemma in running this program. The focus of the study identified the consistency of early childhood education teachers in implementing e-learning programs during the Covid-19 pandemic. Using quantitative methods with purposive sampling technique. Data obtained through interviews (G-Form) with respondents 50 ECE teachers in the city of Surakarta. Field facts are that there is no teacher consistency in implementing e-learning programs such as the absence of daily or weekly learning plans in implementing e-learning, uncertain teaching schedules, and unsupported learning media. This shows that 80% of ECE teachers implement e-learning and 20% implement mixed learning. Teacher consistency can be improved through training provided by the government, provision of educational facilities by schools, learning innovations according to health protocols and initial motivation to teach